Did judge dismiss coach's age discrimination claim?. Issue 4 (8th July 2021) - Lyerly, Eric
Abstract : Indiana University at South Bend's athletics department began searching for a full‐time baseball coach. They desired a coach who would prioritize successful recruiting, student‐ athlete success off the field, and follow university policy.